Effects of vertical position on trematode parasitism in larval anurans. Issue 6 (8th February 2019) - Jones, Jacob R; Steenrod, Camille L; Marino, John A
Abstract: Spatial distributions of animals can affect interactions with their natural enemies, such as parasites, and thus have important implications for host–parasite dynamics. While spatial variation in infection risk has been explored in many systems at the landscape scale, less attention has been paid to spatial structure at smaller scales. Here, we explore a hypothesized relationship between a common spatial variable, vertical position, and risk of parasite infection in a model aquatic system, larval frogs ( Rana ) and trematode (Digenea) parasites. Vertical position is relevant to this system given evidence that the densities of snail first intermediate hosts, tadpole second intermediate hosts, and trematode infective stages can vary with depth. To test the effects of depth on infection risk of larval frogs by trematodes, we performed two enclosure experiments, one in the laboratory and one in the field, in which larval frogs in cages just below the water surface or near the bottom of the water column were exposed to parasites. Compared with near-surface cages, mean infection load (number of cysts) in tadpoles in near-bottom cages was 83% higher after 48-h exposures in the laboratory and 730% higher after 10-day exposures in the field. Our findings thus indicate that infection risk depends on depth, which may have adaptive significance, as tadpoles have previously been shown to change vertical position in response to parasite presence. These results motivate future work examining vertical variation in infection risk and may have broader implications for host–parasite dynamics and evolution of host and parasite behavior.